Transformación e impacto de la industria 4.0 en la logística internacional y una cadena de valor más eficiente (2024)
This monograph focuses on the integration of innovation and the impact of Industry 4.0 in international logistics and value chains, in a dynamic global environment where efficiency and agility are essential, this study explores how emerging logistics technologies Industry 4.0 are fundamentally changing international supply chain management. This study not only aims to provide theoretical knowledge, but also offer practical recommendations for organizations seeking to improve their operational efficiency and competitiveness in the globalized economy, by strategically implementing Industry 4.0 innovations, companies will be able to redefine their logistics operations and maximize the value at each stage of the value chain, ensuring sustainable growth and long-term competitive advantage.